P152 Pulmonary Embolism Rule-out Criteria in Clinical Practice. (14th November 2013) - Scully, PR; McLoughlin, M; Dewar, D; Gossage, J; Aitken, E; Dunn, J
Abstract : Suspected pulmonary embolism (PE) is a common reason for referral to the medical team on call. The pulmonary embolism rule-out criteria (PERC) is a validated scoring system to identify patients at low risk of PE, allowing for possible discharge from the Emergency Department (ED) prior to referral. It is potentially advantageous over the modified Well's score (MWS) for PE, as a D-dimer result is not required. We aimed to investigate two practice models: the PERC and the MWS in the investigation of suspected PE. Those patients referred to the medical team on call by the University Hospital Lewisham ED with a suspected PE were identified over a 3 month period (January to March 2012). Further information was gathered on each patient by review of their ED notes. Patients who did not meet all 8 PERC criteria or had a MWS >4 were considered to be at high risk for PE. 94 patients were identified. The mean age was 53 years (range 18–92) and 68 were female (72%). 9 PEs were diagnosed. 13/94 patients met all PERC criteria, among these no PEs were diagnosed. This group underwent 10 D-dimer tests (70% positive), 2 CTPAs, and 3 V/Q scans. The overall length of stay directly related to waiting for these tests was 6 days, with a mean admission length of 1.3 days per patient.When all PERC criteria were not met due to age (>50 years) alone, the D-dimer proved an excellent 'rule-out' test, as the 2 patients in this cohort with PEs, had strongly positive D-dimer results. Using MWS, 32/94 patients scored >4. Among this group there were 4 confirmed PEs (13%) and 1 indeterminate V/Q result. In the 62 patients with a MWS =4 there were also 4 confirmed PEs (6%), each with a positive D-dimer. PERC is a useful scoring system to identify patients unlikely to have a PE and seems advantageous over the MWS in terms of reducing unnecessary admissions and investigations, while maintaining patient safety. When the PERC criteria are not met due to age alone, a negative D-dimer may also be an effective 'rule-out' option.